Sāk vitt ok vītt of verǫld hverja - Performance - Koutsomichalis, Marinos (My University, 2019)
A hybrid performance, and a film, pivoting on a multi-level exploration of the North Nordic landscape and the artist’s own personal (un)makings of, and creative responses to, it, in terms of photography, video/audio recordings of various acoustic, electromagnetic, geophysical, and anthropological phenomena, text, stones, seafood, and scientific sonification/visualization of data concerning energy consumption, weather change, seismic activity, fish migration, and spatial distribution of marine population.